2017
DOI: 10.5530/ijper.51.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anxiety among Female Governmental Secondary Schools Students in Al-madinah, Saudi Arabia

Abstract: Aim:The study aimed to measure the prevalence and risk factors of Anxiety among Female Governmental Secondary schools students, in Al-Madinah, Saudi Arabia. Methods: Cross sectional study was conducted in Al-Madinah city in 2014. Only Female secondary school students were included for study. Multistage sampling technique was used for student's inclusion. The researcher used a self-administered questionnaire containing socio-demographic data and anxiety questionnaire developed by AL-Taif Mental Health sector. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…This high prevalence of anxiety among females is in keeping with the findings of some other studies [33,38,39]. This study also demonstrates that students of class 9 suffer most (45.3%) from anxiety, which is similar to the findings of other studies [40,41].…”
Section: Plos Onesupporting
confidence: 92%
“…This high prevalence of anxiety among females is in keeping with the findings of some other studies [33,38,39]. This study also demonstrates that students of class 9 suffer most (45.3%) from anxiety, which is similar to the findings of other studies [40,41].…”
Section: Plos Onesupporting
confidence: 92%
“…The current systematic review included 33 studies ( Table 1 ) [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , 45 , 55 , 56 , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [77] , [78] , [79] , [80] ].…”
Section: Resultsmentioning
confidence: 99%
“…Al-Qahtani and Al-Harbi investigated 347 female students for anxiety [ 34 ]. Overall, anxiety was found to be prevalent in 64.3% of the samples with 39% of them having high non-morbid anxiety and 25% with high morbid anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…In adolescents, even higher figures were reported; 17% among Polish adolescents [24], 24% in Pakistan [25], 20.9% among Turkish adolescents [26], 17.7% in Jordan [27] and 9.3% in Egypt [28] In Saudi Arabia, a limited number of recent studies regarding the subject of social anxiety disorder in adolescents was found. AL-QAHTANI & SBFM, conducted a study in 2012 on secondary male students and found that 14% of them had SAD [29]. Another study was conducted in 2013 on secondary school boys which found that 11.7% of the students had SAD [16].…”
Section: Discussionmentioning
confidence: 99%